Pembentukan Karakter Siswa melalui Pembelajaran Pendidikan Agama Islam: Character Building of Students through Islamic Religious Education Learning - Aditya Maulana, Aldikha; Purba, Hadis (Thawalib: Jurnal Kependidikan Islam, 2024)
This study aims to describe the implementation of Islamic Religious Education learning in the character building of students at Public Middle School 1 Percut Sei Tuan. This study uses a qualitative research method with a descriptive type. The techniques used in the study are observation techniques, interviews, and documentation studies. The analysis techniques used: were data reduction, data visualization, and drawing conclusions/verification. The results of this study indicate that: 1) The implementation of Islamic Religious Education learning in the formation of student character through habituation and role models from teachers, performing Dhuha prayers in congregation, and flag ceremony activities. 2) Supporting factors for the formation of student character include internal factors that come from within the individual himself. While external factors are the influence of society, educational regulations, integrated curriculum, evaluation of learning experiences, and parental guidance. Furthermore, inhibiting factors in the implementation of student character formation come from differences in students themselves, differences in backgrounds owned by students, some students whose parents are always at home, and also some students whose parents travel abroad to work.